Penerapan Model Pengembangan Jiwa Kewirausahaan Bagi Murid Sekolah Dasar Negeri 11 Lenteng Agung Jakarta Selatan - Andriyanty, Reny; Hasibuan, Ahmad Nurdin; Rambe, Delila; Wahab, Dodi; Widayati, Enny; Yunaz, Haswan; Damayanty, Prisila; Laksono, Rudi; Rambey, Tagor; Widjanarko, Widjanarko (Jurnal Pengabdian Teratai, 2020)
The Application of Entrepreneurial Concept Development Model For Student in Elementary School Number 11 Lenteng Agung, South Jakarta. The program objection embeded the entrepreneurial concept among elementary school students.The nature of the activity is the pioneering program. The programme was developed by a counseling activity using the playing and question/answer method. The program consists of seven main stages which are implemented by the storytelling method to students. The first stage explained the concept of the entrepreneurial profession, the second stage focused on increasing motivation to become a suscessfull entrepreneur, the third stage is focused on finding business ideas, the fourth stage is teached that getting capital is easy, the fifth stage focused to how to start production, the sixth stage is focused on managing marketing, and the seventh stage focused on the introduction of simple accounting and tax concepts. The advantage of these program was measured by changes of student aspiration. At the beginning, the students who want to become entrepreneurs are zero percent. At the end of the program, the number of students who wanted to become entrepreneurs increased to twenty percent.